2020
DOI: 10.1177/0960327119899987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat-killed Enterococcus faecalis EF-2001 on ethanol-induced acute gastric injury in mice: Protective effect of EF-2001 on acute gastric ulcer

Abstract: Enterococcus faecalis is a facultative anaerobic gram-positive commensal bacterium common in the gastrointestinal tract of animals and humans. This study aimed to investigate the protective effects of heat-killed E. faecalis EF-2001 (EF-2001) on acute gastric ulcer using a murine model of ethanol (EtOH)-induced acute gastric injury. EF-2001 (20, 40, and 80 mg/kg/day) was administered by oral gavage for 5 days before EtOH treatment (10 mL/kg body weight). EF-2001 effectively attenuated EtOH-induced gastric muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Mucosal damage may occur when the toxic factors such as gastric acid, pepsin, bile acid, ethanol, Helicobacter pylori and nonsteroidal anti-inflammatory drugs (NSAIDs) invade and exceed the defense function load of gastric mucosa (Guth et al, 1979;Lee et al, 2017;Khan et al, 2018). Some other factors, such as inadequate dietary habits, excessive ethanol consumption, cigarette smoking, stress and hereditary predisposition, also may lead to the development of GU (Søreide et al, 2015;Jeon et al, 2020). Yet, the clinical treatment for the disease focuses on the use of antisecretory drugs such as H2 receptor antagonist (cimetidine) or proton pump inhibitors (omeprazole), antibiotics (clarithromycin), antacids (aluminum hydroxide), prostaglandin analogues and mucosal protective agents (bismuth) currently (Wallace, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mucosal damage may occur when the toxic factors such as gastric acid, pepsin, bile acid, ethanol, Helicobacter pylori and nonsteroidal anti-inflammatory drugs (NSAIDs) invade and exceed the defense function load of gastric mucosa (Guth et al, 1979;Lee et al, 2017;Khan et al, 2018). Some other factors, such as inadequate dietary habits, excessive ethanol consumption, cigarette smoking, stress and hereditary predisposition, also may lead to the development of GU (Søreide et al, 2015;Jeon et al, 2020). Yet, the clinical treatment for the disease focuses on the use of antisecretory drugs such as H2 receptor antagonist (cimetidine) or proton pump inhibitors (omeprazole), antibiotics (clarithromycin), antacids (aluminum hydroxide), prostaglandin analogues and mucosal protective agents (bismuth) currently (Wallace, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, each mouse is best given 307.5 mg/kg/day probiotics. With reference to previous animal experiments [ 16 , 17 , 18 ], we reduced the dose to 200 mg/kg/day. In the same way, the dose of orlistat in mice was calculated to be 60 mg/kg/day.…”
Section: Methodsmentioning
confidence: 99%
“…A probiotic strain of E. faecalis EF-2001 was isolated from healthy human feces and characterized. It has been reported that EF-2001 possesses radioprotective, antitumor, anti-chronic enteritis, and anti-atopic dermatitis properties [ 15 , 16 , 17 , 18 ]. In this way, EF-2001 can be used without the risk of infection or antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Heat-killed probiotics, such as Enterococcus faecalis , and fractionated cell components, such as cell wall preparations from Lactobacillus spp. and lysate from L. plantarum or L. casei , enhance host resistance and stimulate innate immune responses ( 15 18 ).…”
Section: Introductionmentioning
confidence: 99%